2015
DOI: 10.1016/j.compstruct.2015.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Crush responses of composite cylinder under quasi-static and dynamic loading

Abstract: General rights Copyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. AbstractDespite the abundance of studies investigating the performance of composite structures under crush loading, disagreement remains in the literature regarding the effect of increased strain rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(55 citation statements)
references
References 31 publications
3
51
0
1
Order By: Relevance
“…Similar observations could also be found in literatures [4; 8; 17; 18]. Besides, Chiu et al [2] investigated the behavior of a composite energy absorber made of carbon/epoxy under static and dynamic loading with a strain rate of 0 to 100 ‫ݏ‬ ିଵ . It was shown that the energy absorption was found to be independent of strain rate.…”
Section: Introductionsupporting
confidence: 69%
“…Similar observations could also be found in literatures [4; 8; 17; 18]. Besides, Chiu et al [2] investigated the behavior of a composite energy absorber made of carbon/epoxy under static and dynamic loading with a strain rate of 0 to 100 ‫ݏ‬ ିଵ . It was shown that the energy absorption was found to be independent of strain rate.…”
Section: Introductionsupporting
confidence: 69%
“…6a. These are consistent with the findings by Palanivelu et al [23] and Chiu et al [24]. In the 0˚ plies, the main forms of failure are ply splitting and brittle fibre fracture via bending or shearing.…”
Section: Typical Damage Modessupporting
confidence: 82%
“…Chiu et al [19] investigated the response of a tulip-triggered cylindrical energy absorbing structure undergoing crushing at increasing strain rates. In their work, the energy absorption was found to be independent of strain rate as the total energy absorption appeared to be largely associated with fiber-dominated fracture, which is independent of strain rate within the studied range.…”
Section: Introductionmentioning
confidence: 99%